Histological characteristics of matrix metalloproteinase‐9 and tissue inhibitor of metalloproteinases‐1 in asthmatic murine model during A(H1N1)pdm09 infection. Issue 10 (6th September 2022) - Kimura, Sasagu; Yasudo, Hiroki; Oga, Atsunori; Fukano, Reiji; Matsushige, Takeshi; Hamano, Hiroki; Hasegawa, Hideki; Nakajima, Noriko; Ainai, Akira; Itoh, Hiroshi; Shirabe, Komei; Toda, Shoichi; et al.
Abstract: Pandemic influenza virus A(H1N1)pdm09 infection occurred in healthy children and young adults, but asthmatic patients presented more rapid progression of respiratory distress and plastic bronchitis. To investigate the pathogenesis of worsening respiratory symptoms after A(H1N1)pdm09 infection, we focused on matrix metalloproteinase‐9 (MMP‐9) and tissue inhibitor of metalloproteinases‐1 (TIMP‐1). MMP‐9 and TIMP‐1 levels in bronchoalveolar lavage fluid and serum from mice with and without asthma were evaluated after A(H1N1)pdm09 or seasonal A(H1N1) infection. MMP‐9 levels were more elevated in Asthma/A(H1N1)pdm09‐infected mice than in non‐Asthma/A(H1N1)pdm09‐infected mice on both 3 and 7 days post‐infection. Immunohistochemical findings in this pneumonia model showed that MMP‐9 and TIMP‐1 positive cells were observed in blood vessels and bronchus of lung tissue in severe pathological findings of pneumonia with asthma. Microscopically, shedding cells and secretions were conspicuous in the trachea on days 3 and 7 post‐infection, in the A(H1N1)pdm09‐infected mice with asthma. Our results suggest that MMP‐9 and TIMP‐1 expressions are related to severe pneumonia in the A(H1N1)pdm09 infection with asthma, leading to cause epithelial cell shedding.